Consolidation, Translation, and the Equity Method: Concepts and Procedures. - Mead, George C.; Hendrickson, Harvey S. (The Accounting Review, 1987)
Reviews the book 'Consolidation, Translation, and the Equity Method: Concepts and Procedures,' by Paul Rosenfield and Steven Rubin.